Effects of Early-Age rheology and printing time interval on Late-Age fracture characteristics of 3D printed concrete - Wu, Yun-Chen; Li, Mo (Construction & building materials, 2022)
•Fracture of 3D printed concrete is strongly affected by rheology and printing process.•Increasing printing time interval changes rheology and decreases fracture toughness.•Time effect is stronger on fracture characteristics of interlayers than filaments.•Dynamic oscillation sweep method reveals time-dependent storage modulus and viscosity.•Novel fracture experiment using DIC measures and visualizes process zone growth. Concrete additive manufacturing, also known as 3D printing, opens tremendous opportunities in the construction industry, architectural design, defense and space exploration. As concrete is a quasi-brittle material and prone to fracture, it is crucial to understand the effect of the layer-by-layer manufacturing process, such as the variation in printing time intervals and the introduction of printing interlayers, on the fracture behavior of 3D printed concrete. This study elucidated the effects of early-age material rheology, printing time interval and printing path on the late-age load versus crack mouth opening displacement relation, fracture process zone, fracture toughness and fracture energy of 3D printed concrete materials with notch locations at interlayers vs filaments. A dynamic oscillation stress sweep method was used to reveal the time-dependency of early-age rheological parameters. A novel fracture experiment was designed to integrate a digital image correlation system to enable closed-loop control, measurement, and visualization of crack tip parameters during the rapid fracture processes along the printing interlayers or filaments. The results revealed that the fracture characteristics of 3D printed concrete are strongly influenced by its rheology and time-dependency of rheology, which is fundamentally different from normal cast concrete. Increasing the printing time interval increases the storage modulus, yield stress and complex viscosity of 3D printed concrete materials at different shear stress levels, consequently increasing the likelihood of imperfections, and thus decreasing the maximum process zone size developed at the crack tip, fracture toughness and fracture energy of 3D printed concrete. Such effects were found to be stronger on the fracture characteristics of printing interlayers than filaments.